Robust Position Control of Electro-mechanical Systems - Rong Mei; Mou Chen (Institute of Advanced Engineering and Science, 2013)
In this work, the robust position control scheme is proposed for the electro-mechanical system using the disturbance observer and backstepping control method. To the external unknown load of the electro-mechanical system, the nonlinear disturbance observer is given to estimate the external unknown load. Combining the output of the developed nonlinear disturbance observer with backstepping technology, the robust position control scheme is proposed for the electro-mechanical system. The stability of the closed-loop control system has been proved via the Lyapunov analysis technique. Simulation results are presented to demonstrate the feasibility of the proposed disturbance-observer-based position control scheme of the electro-mechanical system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2323